(untitled) (The Review of Diabetic Studies, 2025)
This review explores the critical role of advanced prehospital interventions performed by paramedics in enhancing patient survival during life-threatening emergencies. These interventions—ranging from advanced airway management, rapid sequence intubation (RSI), mechanical chest compression devices, tranexamic acid (TXA) administration, and prehospital blood transfusion—are transforming emergency medical care worldwide. The review systematically analyzes evidence from observational studies, randomized controlled trials, and systematic reviews published over the past decade. Findings reveal that timely advanced interventions significantly improve neurological outcomes, hemodynamic stability, and overall survival rates, particularly in trauma, cardiac arrest, and severe respiratory failure. Furthermore, the integration of point-of-care diagnostics, telemedicine support, and AI-driven decision tools enhances clinical precision and response efficiency. The study concludes that empowering paramedics with advanced clinical autonomy, continuous simulation training, and protocol-based decision support systems is essential to reduce mortality in prehospital emergencies.